2014
DOI: 10.1557/mrs.2014.248
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating nano-bio interactions: A spectroscopic perspective

Abstract: IntroductionEngineered nanomaterials (ENMs) provide much-needed breakthroughs for resolving some longstanding challenges in drug delivery and personalized medicine. They exhibit pronounced interactions with biomolecules and the ability to effi ciently cross many physiological barriers due to their small size, which may also cause undesired side effects (also see the Wick et al., Hemmer et al., and Bhattacharya et al. articles in this issue). 1 -5 Spectroscopic tools can be used to determine the underlying bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…[2][3][4][5][6][7] Although concerted efforts from researchers across the globe have led to a better understanding of nanomaterial toxicity, the fundamental mechanisms through which nano-bio interactions occur still remain largely inconclusive. 8 Building on the understanding of adsorbed biomolecules in cellular responses to biomaterials, a new picture of nanotoxicity based on protein-nanomaterial interactions is recently beginning to emerge. [7][8][9][10][11][12] Once placed in a physiological environment, the surface of nanomaterials becomes coated with various biomolecules including proteins, peptides, and lipids, collectively referred to as the "corona".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7] Although concerted efforts from researchers across the globe have led to a better understanding of nanomaterial toxicity, the fundamental mechanisms through which nano-bio interactions occur still remain largely inconclusive. 8 Building on the understanding of adsorbed biomolecules in cellular responses to biomaterials, a new picture of nanotoxicity based on protein-nanomaterial interactions is recently beginning to emerge. [7][8][9][10][11][12] Once placed in a physiological environment, the surface of nanomaterials becomes coated with various biomolecules including proteins, peptides, and lipids, collectively referred to as the "corona".…”
Section: Introductionmentioning
confidence: 99%
“…8 Building on the understanding of adsorbed biomolecules in cellular responses to biomaterials, a new picture of nanotoxicity based on protein-nanomaterial interactions is recently beginning to emerge. [7][8][9][10][11][12] Once placed in a physiological environment, the surface of nanomaterials becomes coated with various biomolecules including proteins, peptides, and lipids, collectively referred to as the "corona". Previously, others and we have shown that…”
Section: Introductionmentioning
confidence: 99%
“…1, 9, 18 Despite this obvious importance of defects and charge transfer in CNM toxicity, the influence of structural and functional defects in CNMs on biomolecular adsorption and immune response remains poorly understood. 21 Although the formation of protein corona on CNMs has been extensively studied in recent years, the underlying physical and chemical processes in protein and defected CNM interactions (e.g., charge transfer between proteins and defects) have not yet been completely understood. To elucidate the role of defects and their associated charge transfer in biological interactions of CNMs, it is imperative to synthesize CNMs with different defect content and study their effects on protein corona.…”
Section: Introductionmentioning
confidence: 99%
“…19 Indeed, charge transfer interactions between proteins and CNMs have previously been implicated in destabilizing adsorbed proteins/enzymes, which could in turn elicit adverse physiological response. 9,21 While the root cause of ENM (particularly CNM) toxicity is still a subject of ongoing research, numerous studies have identied the presence of bioactive defects in ENMs (including Au, Ag, TiO 2 , SiO 2 , and CNMs) as the common denominator in their physiological response. 1,[12][13][14][15] In case of CNMS, it has been hypothesized that the presence of neutral and charged defects could elicit an adverse physiological response possibly by generating highly reactive oxygen species and inducing structural changes in proteins through charge transfer reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Conducting a study in real biological fluids is difficult as there are many molecules which compete for binding sites on a nanoparticle surface, and the dynamic nature of the protein corona creates much variability in the precise composition at any time [52]. Furthermore, analyzing which protein or ion is adsorbed to the surface is difficult without trained scientists and expensive techniques [45,103,104]. Thus, a model protein can be used to investigate the nature of the protein corona in a simple aqueous medium to develop an understanding about the overall nature of the protein corona.…”
Section: In Vitro Studies With Nanoparticles and Lung Cellsmentioning
confidence: 99%